Modification of the drug resistance of emerging milk-borne pathogens through sodium alginate-based antibiotics and nanoparticles - Manan, Abdul; Aqib, Amjad Islam; Shahbaz, Ansa; Khan, Shanza Rauf; Akram, Kashif; Majeed, Hamid; Muneer, Afshan; Murtaza, Maheen; Afrasiab, Muhammad; Merola, Carmine; Niaz, Kamal; Ahmad, Irfan; et al. (Frontiers in Veterinary Science, 2023)
Milk-borne bacteria have been a serious concern for the health of animals and the public Moreover, considering Streptococcus agalactiae (S. agalactiae) and Klebsiella pneumoniae(K. pneu-moniae) as minor contaminants of milk have made the situation graver with special context to rise in antimicrobial resistance. The current study was thus planned to investigate the prevalence of S. agalactiae and K. pneumoniae from mastitis milk samples, their drug resistance profile, and to assess sodium alginate (G) stabilized MgO nanoparticles (M) and antibiotics (tylosin T, ampi-cillin A) as a modified approach to tack resistance. The findings of the current study revealed 28.42% of mastitis samples were positive for S. agalactiae and K. pneumoniae while increasing re-sistance was found against antibiotics. Response of four preparations GT (Gel stabilized tylosin), GA (gel-stabilized ampicillin), GTM (tylosin and MgO nanoparticles stabilized in gel), and GAM (Ampicillin and MgO stabilized in gel) on the other hand produced significant resistance modulation in both bacteria. The percentage increase in the zone of inhibition (ZOI) was shown by all preparation compared to the use of antibiotics alone while GTM presented 59.09% and 56.25% higher ZOI against S. agalactiae and K. pneumoniae, respectively. The lowest MIC against K. pneumoniae was found to be 9.766±0.0 µg/mL as expressed by GTM followed by GT, GAM, and GA after 24 hours of incubation. A similar response was noted but a compara-tively higher number of MICs of preparations against S. agalactiae. A significant reduction in MIC with respect to incubation time was found after 8th hr and remained until 20th hr of incubation against both of pathogens. Cytotoxicity of MgO nanoparticles was found significantly lower to that of positive control. The study thus found emerging resistance in K. pneumonia and S. agalactiae from dairy milk while sodium alginate-based antibiotics and MgO nanoparticles proved significant resistance modulators.